Intervenciones Farmacéuticas en pacientes con Diabetes Mellitus Tipo 2 - Maidana, Gladys Mabel; Vera, Zully; Samaniego, Lourdes; Acosta, Patricia; Mastroianni, Patricia [UNESP]; Lugo, Gladys Beatriz (My University, 2017)
Introduction: Pharmaceutical Care is the responsible provision of the pharmacotherapy with the purpose of achieving concrete results in order to improve the quality of life of the patients. Objective: To evaluate the impact of pharmaceutical intervention on patients with Type 2 Diabetes Mellitus. Methodology: Random Clinical Assay with measurement of variables before and after. Non probabilistic. At convenience. Participating population was composed of 32 patients at the intervention group and 32 at the control group. Monthly interviews were performed in a period of pharmaceutical intervention of 6 months (from October 2011 to June 2012). In this period they were recorded only 3 dropouts. Results: The patients' age was 55.6 ± 10.6 years. Patients in the intervention group improved glycaemia in 34%, where 24 patients had the value (≤ 130 mg / dL); the glycosylated hemoglobin improved 1.9%, where 15 patients achieved the desired parameters (≤ 6.5%). The quality of life of the intervention group increased from (56.3 to 71.3%) and was measured with the SF-36 questionnaire. In the intervened group, 80 drug-related problems were found; in 27 patients, 59 were resolved; at the end of the study 12 patients resolved all drug-related problems; 254 pharmaceutical interventions were performed, the level of patient knowledge about the disease improved by 41%, knowledge about their medications improved by 53%. Conclusion: Pharmaceutical interventions improved the clinical parameters of glycemia, glycosylated hemoglobin, optimized drug use, decreased drug-related problems, and improved the quality of life of patients.
Pharmaceutical interventions in patients with Type 2 Diabetes Mellitus
Keywords: Pharmaceutical Care; Pharmaceutical Intervention; Type 2 Diabetes Mellitus